Effect of Coenzyme Q10 on the reproductive system of female rats (Rattus norvegicus ) treated with lead acetate - Al- Rumaidh, Shaymaa Zgher; Al-Zamely, Hayder A. (Journal of Kerbala for Agricultural Sciences, 2017)
This study was conducted to evaluate the effectiveness of the CoQ10 on the reproductive system of female rats and it's ability to reduce the harmful effect of lead acetate. To achieve this goal an experiment was done on 24 mature female rats which are randomly divided into 4 groups, group(1) treated with 1ml/kg corn oil and considered as a negative control group, group(2) treated with CoQ10 at dose 200 mg/kg and considered as a positive control group, group(3) treated with lead acetate at dose 8mg /kg ,and group (4) treated with lead acetate for 30 days then after CoQ10 for another 30 days. Blood samples were taken from all animals after 60 days for biochemical analysis to estimate FSH, LH, estrogen and progesterone hormones .Histological examinations of an ovary and uterus were also involved in this study. Results showed a significant increase (p< 0.05) in serum FSH, estrogen and progesterone levels in group(2) compared to other groups while LH level was significantly increased (p< 0.05) compared to group (3). Group( 3) showed a significant decrease (p< 0.05) in serum FSH, LH level in compared to group (1) and group( 4 ),while progesterone and estrogen levels showed no significant difference (p> 0.05) compared to group(1) . At the same time, there were no significant difference (p> 0.05) in serum LH, estrogen and progesterone levels in group (4) compared to group(1), while there was a significant decrease (p< 0.05) in serum FSH level in group(4) compared group(1). The results of ovary sections ,group( 2) showed normal structure and distribution pattern of various ovary components, while group (3)showed sever hemorrhage in the ovarian stroma and suppression of ovarian follicles. Group(4) showed particular recovery in ovarian parenchyma. Uterus sections of group(2) showed normal epithelium which lining the uterus and there is destitution uterine glands. Group(3) showed epithelium degenerative, small and non developed uterine glands and hemorrhage in uterine tissue .Other wised uterus in group (4)showed normal columnar epithelium which lining the uterus, and proliferation of uterine glands.